ANALYSIS OF SURFACE GILLNET FISHING GEAR AT BAGAN SIAPI-API WATERS, INDONESIA USING EAFM INDICATORS - Rahmad Dharmawan; Agus Suherman; Abdul Kohar Mudzakir (Marine Fisheries : Journal of Marine Fisheries Technology and Management, 2022)
The fisheries management based on the Ecosystem Approach to Fisheries Management (EAFM) can be implemented to optimize the potential of fisheries resources. The purpose of this research is to apply EAFM indicators for analyzing surface gillnet fishing gear in Bagan Siapi-api waters, especially fish resources, fishing methods, habitats, and ecosystems. The evaluation of fishery management status was carried out using multi-criteria analysis (MCA) through the development of the composite index of each EAFM indicator. The results showed that the surface gillnet fishing gear was dominant with 1,645 tons of fish caught in 2019 by fishermen in Bagan Siapi-Api Waters. The composition of the catches was sukain fish (Eleutheronema tetradactylum), flounder fish (Pleuronectiformes), and tornfish (Bovichthyidae). Based on the analysis of the EAFM indicators, the value of the domain of fish resources, habitats, and ecosystems, as well as fishing methods has a value between 2 and 2.5. This indicated that the status of ecosystem-based area management in the waters of Bagan Siapi-api is in the medium-good category. Keywords: Bagan Siapi-api, EAFM, Fisheries Sustainability, Gill Net